Intrinsic reaction coordinate: Calculation, bifurcation, and automated search. Issue 5 (3rd September 2014) - Maeda, Satoshi; Harabuchi, Yu; Ono, Yuriko; Taketsugu, Tetsuya; Morokuma, Keiji; Nakai, Hiromi; Tsuneda, Takao
<x xml:space="preserve">Abstract</x> The intrinsic reaction coordinate (IRC) approach has been used extensively in quantum chemical analysis and prediction of the mechanism of chemical reactions. The IRC gives a unique connection from a given transition structure to local minima of the reactant and product sides. This allows for easy understanding of complicated multistep mechanisms as a set of simple elementary reaction steps. In this article, three topics concerning the IRC approach are discussed. In the first topic, the first ab initio study of the IRC and a recent development of an IRC calculation algorithm for enzyme reactions are introduced. In the second topic, cases are presented in which dynamical trajectories bifurcate and corresponding IRC connections can be inaccurate. In the third topic, a recent development of an automated reaction path search method and its application to systematic construction of IRC networks are described. Finally, combining these three topics, future perspectives are discussed. © 2014 Wiley Periodicals, Inc.